Measuring Success of Meditation, Curcumin Supplementation and Sunlight Exposure among Office Workers with Mild Depression - Chirra Taworntawat; Karl J. Neeser; Ratana Somrongthong; Timothy E. O’Brien (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Globally, major depression is the primary cause of disability, where a large part of cases is reportedamong the working-class.Methods: We conducted comparative cross-sectional study with 8-week observation includes mindfulnessmeditation, curcumin supplementation and sunlight exposure (MCS program) among mildly depressed officeworkers of both sexes - 34 in observed group (OG) and 34 in control group (CT). At baseline, day 30, andday 60, participants were compared in terms of (a) vitamin D, (b) brain-derived neurotrophic factor (BDNF), (c)interleukin-6 (IL-6), and (d) depression scores using PHQ-9. ELISA were performed for all serum samples.Results: The rates of increase of vitamin D in both day 0, 30 and day 30, 60 intervals were significantly higher inOG (p<0.05). BDNF levels varied extensively between the groups. IL-6 means were significantly lower in OG atday 30 than in CG (p<0.05). Depression scores rate of change demonstrated appreciable fall in day 0, 30 intervaland stayed down to day 60 in OG. Significantly, lower depression scores were observed for OG at both day 30 andday 60 (p<0.05).Conclusion: MCS program resulted in significant decreases in depression scores and some of its related biomarkers, thus can be a sustainable and cost-effective approach to alleviating psychological depression among the working-class.